1976
DOI: 10.1113/jphysiol.1976.sp011559
|View full text |Cite
|
Sign up to set email alerts
|

Gastric emptying of organic acids in the dog.

Abstract: SUMMARY1. Test meals of 300 ml. of six different organic acids were instilled into the stomach of six healthy mongrel dogs. Citric, acetic, propionic, lactic, tartaric and succinic acid were given in 50, 100, 150 and 200 mN concentrations.2. During the emptying process, the gastric contents were aspirated and immediately re-instilled at 10 min intervals, and the following parameters were recorded: volume, concentration of the organic anion, pH, hydrogen ion concentration and osmolarity.3. By multiple stepwise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

1980
1980
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…Also, in the rat study, the glucose response showed a slower decrease in the late postprandial phase in the presence of the acid, which is in line with a mechanism related to a lowered gastric emptying rate (Ebihara & Nakajima, 1988). In studies from the 1960s and 1970s, the influence of organic acids on gastric emptying was evaluated in both humans (Hunt & Knox, 1969, 1972 and animals (Blum et al, 1976). In one of these early reports, Hunt and Knox (1972) stated that the higher the molecular weights of weak acids, the lower the potential of slowing gastric emptying.…”
Section: Discussionmentioning
confidence: 68%
“…Also, in the rat study, the glucose response showed a slower decrease in the late postprandial phase in the presence of the acid, which is in line with a mechanism related to a lowered gastric emptying rate (Ebihara & Nakajima, 1988). In studies from the 1960s and 1970s, the influence of organic acids on gastric emptying was evaluated in both humans (Hunt & Knox, 1969, 1972 and animals (Blum et al, 1976). In one of these early reports, Hunt and Knox (1972) stated that the higher the molecular weights of weak acids, the lower the potential of slowing gastric emptying.…”
Section: Discussionmentioning
confidence: 68%
“…With respect to beneficial effects on glucose metabolism, Todesco et al (1991) suggested that the reduction seen in postprandial glycaemia following ingestion of propionateenriched bread was caused by an inhibition of the amylolytic activity. Other possible mechanisms include a delay in the rate of gastric emptying in mammals, including man (Blum et al 1976; H. Liljeberg and I. Bjorck, unpublished results). In addition, propionic acid has been shown to increase glycolysis and decrease glucose production in isolated rat hepatocytes (Anderson & Bridges, 1984).…”
mentioning
confidence: 93%
“…3 The volume of an ingested fluid meal is the most important determinant of the emptying rate in monogastric animals 4 and suckling calves. 5 Other physiologically important determinants of emptying rate are energy density (ie, caloric content) of a meal, [6][7][8] type of protein or fat, [9][10][11] and osmolarity of the solution. 12 Because an increased caloric content of an ingested meal slows gastric emptying rate, [6][7][8] we hypothesized that an OES containing a high-glucose concentration would be emptied more slowly in suckling calves than a low-glucose OES.…”
mentioning
confidence: 99%